2017
DOI: 10.1080/03601234.2017.1405626
|View full text |Cite
|
Sign up to set email alerts
|

Easy and fast extraction methods to determine organochlorine pesticides in sewage sludge, soil, and water samples based at low temperature

Abstract: Organochlorine pesticides present in sewage sludge can contaminate soil and water when they are used as either fertilizer or agricultural soil conditioner. In this study, the technique solid-liquid extraction with low temperature purification was optimized and validated for determination of ten organochlorine pesticides in sewage sludge and soil samples. Liquid-liquid extraction with low temperature purification was also validated for the same compounds in water. Analyses were performed by gas chromatography-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In addition to reducing the signal intensity of the analyte studied, the use of ethyl acetate in the extractor phase also intensified the matrix effect, as evidenced by the high recovery percentages, as shown in Table 1. These results are in agreement with those found by Silva et al 17 who achieved high recovery rates using acetonitrile in the miniaturized version of liquid-liquid extraction with low temperature partition to determine pesticides in biological matrices; and Mesquita et al, 14 who used acetonitrile in SLE-LTP to study various pesticides in soil samples.…”
Section: Optimization Of the Extraction Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to reducing the signal intensity of the analyte studied, the use of ethyl acetate in the extractor phase also intensified the matrix effect, as evidenced by the high recovery percentages, as shown in Table 1. These results are in agreement with those found by Silva et al 17 who achieved high recovery rates using acetonitrile in the miniaturized version of liquid-liquid extraction with low temperature partition to determine pesticides in biological matrices; and Mesquita et al, 14 who used acetonitrile in SLE-LTP to study various pesticides in soil samples.…”
Section: Optimization Of the Extraction Methodssupporting
confidence: 91%
“…[6][7][8][9][10][11][12] Although these methodologies have proven to be very efficient and sensitive, the development of new extraction methods which can be simpler, easier to perform, sensitive, efficient and cheaper is recommended. In this sense, previous works [13][14][15][16] have shown that solid-liquid extraction with low temperature purification (SLE-LTP) has gathered these characteristics when applied to other environmental contaminants. Therefore, a miniaturized variation of this methodology was recently optimized and validated to monitor pesticides in biological matrices.…”
Section: Introductionmentioning
confidence: 98%
“…In this sense, previous works have shown that solid-liquid extraction coupled with low-temperature purification (SLE-LTP) has met these characteristics when applied to other environmental contaminants. 15,16 One of the main advantages of this methodology is the extraction and cleaning in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…In this period, the matrix and its components are entrapped into the structure of ice, while the target analyte migrates to the liquid organic phase, and generally no additional clean-up step is necessary. 11,12 Therefore, the extract may be analyzed by analytical techniques, such as liquid chromatography or gas chromatography. However, to the best of our knowledge, no studies employing this methodology for determining uopyram in water samples have been completed so far.…”
Section: Fluopyrammentioning
confidence: 99%